Diary of a Roblox pro Vol. 4 Lava chase - Avatar, Ari. (New York, NY Scholastic Inc., 2023)
"Ari and his friends have to go on a boring geography field trip to a dormant volcano. Ugh! Ari and his friends sneak off . . . only to get lost. Then they realize their class went home without them! Much to their surprise, Ari, Zeke and Jez also discover that the volcano may not be quite as dormant as they thought. It's time to get out of here! It's the ultimate lava chase adventure in the next unauthorized Roblox Pro book!"--Publisher.
"An unofficial Roblox book"--Front cover.
4.3.
3-6
Keywords: Roblox (Computing platform) -- Juvenile fiction; Best friends -- Juvenile fiction; Games -- Juvenile fiction; Volcanoes -- Juvenile fiction; Adventure stories; Roblox (Computing platform) -- Fiction; Best friends -- Fiction; Games -- Fiction; Volcanoes -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Action and adventure fiction; Fantasy fiction